Monitoring and baseline of glyphosate-resistant sourgrass in the main soybean growing regions of Brazil - Gonçalves Netto, Acácio; Carvalho, Saul Jorge Pinto de; Nicolai, Marcelo; Lopez Ovejero, Ramiro Fernando; Presoto, Jéssica Cursino; Andrade, Jeisiane de Fátima; Resende, Laís Sousa (Revista de Ciências Agroveterinárias, 2022)
Frequent application of glyphosate for consecutive years has enhanced the selection pressure on sourgrass (Digitaria insularis) populations, which resulted in the development of glyphosate-resistant biotypes. Therefore, this work was developed with the objective of monitoring sourgrass resistance to glyphosate, develop a baseline of sourgrass susceptibility to this molecule and, consequently, identify the discriminatory dose between resistant and susceptible populations. This work was divided into three steps. The first step consisted of identifying and sorting sourgrass resistant and susceptible biotypes among 30 samples. In the second step, glyphosate baseline was elaborated considering exclusively the glyphosate-susceptible biotypes, which allowed the definition of a discriminatory dose. At the end, the third step, monitoring of glyphosate-resistant biotypes was achieved, considering five growing seasons (2016 – 2020) and 809 samples of sourgrass populations, collected throughout 12 states of Brazil. Glyphosate baseline was elaborated to sourgrass and ideal discriminatory rate was identified as 960 g ha-1. Glyphosate-resistant populations of sourgrass were found in all soybean growing regions sampled. Among 809 populations, 25.96% were considered resistant to glyphosate. The states with the highest frequency of glyphosate-resistant populations were Rio Grande do Sul, Mato Grosso do Sul, Bahia, Mato Grosso and Paraná.